Peningkatan Kemampuan Literasi dan Numerasi Peserta Didik di SDN 18 Mataram - Mujiburrahman .; Lu'luin Najwa; M Najamuddin; Siti Nur Hadijah (Fakultas Ilmu Pendidikan dan Psikologi, 2024)
Community service was conducted at SDN 18 Mataram, Dasan Agung Baru, Selaparang District. The target of this activity is for the teachers and students of SDN 18 Mataram to improve teaching skills by strengthening literacy and numeracy. In implementing this community service, training and mentoring methods were used, followed by teachers, as well as socialization to students of SDN 18 Mataram. The training consists of two stages, where the first stage involves explaining literacy and numeracy in elementary schools, while the next stage involves mentoring individuals to practice learning related to literacy and numeracy. This training and mentoring runs following the objectives and plans that have been set. This program received a positive response from the Principal and all teachers at SDN 18 Mataram. This activity provides additional knowledge about learning methods and media in the context of strengthening literacy and numeracy for teachers. In the process of teaching and learning activities, teachers will consistently use innovative learning methods and media, so that students can learn optimally.